Is it true that essential tremor affects sleep? A comparison between young essential tremor patients and normal controls - ŞENGÜL, YILDIZHAN; Sengul, YILDIZHAN; SENGUL, Hakan (My University, 2015)
Essential tremor (ET) is the most common movement disorder and cause of functional disability. ET is known as a monosymptomatic, pure motor system disease. This interpretation of ET has been questioned in the last decade. Non-motor symptoms have added to the definition of the disease. In autopsy studies, it has been reported that Lewy bodies are common in the locus coeruleus, which is known to have an active role in sleep. Previous research about sleep in ET has studied older patients. Sleep disturbances are common in older adults. Our study focused on younger patients who had the disease for a shorter period of time. 40 patients (24.9 +/- 7.0 years old) and 28 controls were recruited for the study. Sleep quality was evaluated with the Pittsburg Sleep Quality Index (PSQI). Excessive daytime sleepiness (EDS) was evaluated with the Epworth Sleepiness Scale (ESS). For assessing the possible impact of depression and anxiety on sleep we used the Beck Depression Inventory (BDI), and the Beck Anxiety Scale (BAS). We ruled out other possible causes of tremor. Tremor was evaluated using the Fahn Tolosa Marin Tremor Rating Scale (FTM-TRS). We concluded that although ET patients had bad sleep quality, this might be associated with increased anxiety levels. Mean ESS scores were higher in the patient group, but this was not statistically significant.